Femoro-distal bypass in a 5-year old with blunt popliteal artery trauma: Considerations in a limited resource setting - Michael J Ramdass; Abigail S Cooblal; Ashton Ramsundar; Sushilla Maharaj (Wolters Kluwer Medknow Publications, 2020)
Blunt popliteal vascular injury in the paediatric population is exceedingly rare and in advanced trauma centres the management can be challenging. A case of blunt popliteal artery trauma in a 5 years old requiring distal bypass using reversed saphenous vein is herein described. It is noteworthy to mention the difficulties experienced in a limited resource setting, including limitations in small rural hospitals, inefficient timely transfer to specialised centres, inadequate numbers of highly trained surgeons in subspecialities such as microvascular surgery and finally ineffective support and rehabilitative services.